A Review of Poultry Product as a Source of Spreading Multidrug Resistant Salmonella: Public Health Importance - Fanissa, Farah (Media Kedokteran Hewan, 2022)
In the last few decades, foodborne disease has become one of the world's health problems with various pathogenic bacteria that accompanies the contamination of food products of animal origin. One of the foodborne diseases that is always reported every year is related to Salmonella contamination in poultry products which can cause Salmonellosis in humans. Salmonella contamination become important not because of its virulence ability to invade humans, but also because of its increased resistance to various clinical antimicrobial classes, with various cellular genetic elements that can be spread in humans along the food chain. The purpose of this review is to provide an overview of the role of poultry product in the spread of multidrug resistance Salmonella which may have implications for public health.